Hospital Acquired Diarrhoea in Children: A Study in a Tertiary Care Hospital in Sylhet (Journal of Rangpur Medical College, 2024)
Background: Children hospitalized for diseases other than diarrhoea can be infected with an enteric pathogen during their stay at hospital, which may complicate and prolongs the course of illness and hospital stay. Hospital acquired diarrhoea are defined as those occurring more than 72 hours after admission to hospital. Nosocomial diarrhoea second to nosocomial respiratory tract infections in causing morbidity among hospitalized children. Objectives: The study was designed to find the rate of hospital acquired diarrhoea, their risk factors and to observe the clinical features. Method: This cross-sectional observational study was conducted in the inpatient department of Pediatrics in Jalalabad Ragib-Rabeya Medical College, Sylhet over a period of 3 months between July to September 2018. A total number of 274 children aged from 1 month to 5 years were admitted in inpatient department other than diarrhoea were included in the study. During their hospital stay, all patients were followed up daily for development of diarrhoea. Results: Out of 274 children 80 patients developeddiarrhoea 72 hours after admission, the rate of occurrence of hospital acquired diarrhoea was 29.2%. Patients who developed hospital acquired diarrhoea, were initially admitted due to pneumonia accounted for about 65% followed by 12.5% due to malnutrition. Patients aged below two years and staying in hospital for longer duration developed diarrhoea more. Presence of any diarrhoeal patient in a bed close the patient’s bed (p=0.00001), hand washing by mother’s during handling baby (p=0.00001), hand washing by doctors (p=0.00001), and sharing the bathroom with diarrhoeal patient (p=0.000061), were statistically associated with the development of nosocomial diarrhoea. Diarrhoea was mostly watery in nature (80%) having pus (80%) and RBC (100%) on stool microscopy and patients suffered from milder dehydration (80%). Conclusions: Hospital acquired diarrhoea is common in admitted patients, which may complicate the disease course, prolonged the hospital stay.J Rang Med Col. March 2024; Vol. 9, No. 1: 65-70